2020
DOI: 10.2147/ijgm.s251924
|View full text |Cite
|
Sign up to set email alerts
|

<p>Echocardiographic and Clinical Correlates of Ejection Fraction Among 2000 Patients with Heart Failure in Western Saudi Arabia</p>

Abstract: Introduction: Heart failure (HF) affects about 320,000 Saudi individuals and is associated with a considerable negative impact on the patients' quality of life. In literature, there is a lack of data about the echocardiographic abnormalities of HF patients in Saudi Arabia. Aim of Work: To describe the echocardiographic findings of HF patients in Western Saudi Arabia. Methodology: This was a retrospective record review study conducted on 2000 patients with chronic HF in Saudi Arabia. Demographic, clinical and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…With regard to the dominance of LV reduced EF (despite different cut-off values) and male sex, over those with preserved EF and female sex, these present findings are in agreement with two national studies, 5 , 6 whereas a third study reported an opposite pattern, 7 with Saudi nationals constituting 43.5% of the participants. With respect to BMI, disease severity (NYHA III–IV), underlying IHD, hypertension, therapeutic trends and mortality, there are general similarities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…With regard to the dominance of LV reduced EF (despite different cut-off values) and male sex, over those with preserved EF and female sex, these present findings are in agreement with two national studies, 5 , 6 whereas a third study reported an opposite pattern, 7 with Saudi nationals constituting 43.5% of the participants. With respect to BMI, disease severity (NYHA III–IV), underlying IHD, hypertension, therapeutic trends and mortality, there are general similarities.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of the total number of enrolled HF patients, two studies reported a dominance of patients with reduced EF over those with preserved EF, 5 , 6 while the third reported the opposite. 7 Therefore, this present observational study seeks not only to report the clinical, echocardiographic, and therapeutic characteristics of HF using another representative sample of the Saudi HF population (Eastern province), but also to identify characteristics that may be relevant elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study IVS thickness, a biomarker of hypertension, was signifi cantly higher in patient with LLD suggesting a possible role as a cofactor in the LLD onset. Moreover, hypertension is frequently associated with Mitral Prolapse [50], suggesting a cluster between these two pathological conditions that may have and add on effect on the onset of depression.…”
Section: Group 1 Patients Showed a Higher Cognitive Damage (Mmsementioning
confidence: 99%
“…However, diastolic dysfunction is important, and it should be recognized as early as possible to avoid its progression to diastolic failure. Diastolic dysfunction has been reported to be more prevalent in the patients with heart failure with preserved ejection fraction (HFpEF) as compared to those with heart failure with reduced ejection fraction (HFrEF) [ 9 ]. The reason is that the patients with HFpEF have extensive perivascular fibrosis as compared to those with HFrEF.…”
Section: Introductionmentioning
confidence: 99%